Impact of surgical procedures on soft tissue microcirculation in calcaneal fractures: A prospective longitudinal cohort study. Issue 12 (December 2019) - Bläsius, Felix M.; Link, Björn-Christian; Beeres, Frank J.P.; Iselin, Lukas D.; Leu, Benjamin Moritz; Gueorguiev, Boyko; Klos, Kajetan; Ganse, Bergita; Nebelung, Sven; Modabber, Ali; Eschbach, Daphne; Weber, Christian David; et al.
Highlights: A correlation between the surgical technique and the postsurgical course of sO2 values at the 2 mm depth was found. BF was higher in the ORIF group at the 2 mm and 8 mm depths, and BF increased after surgery in both groups. There was no correlation between the surgical technique and the BF. sO2 at the 2 mm and 8 mm depths was higher in the ORIF group. Furthermore, after surgery, sO2 increased at the 2 mm depth and decreased at the 8 mm depth in both groups. There was no correlation between the surgical technique and the postsurgical course of sO2 values at the 8 mm depth. rHb values did not differ between the ORIF group and the MIA group. rHb values at the 2 mm depth showed no changes after surgery in both groups. rHb values at the 8 mm depth decreased, but there was no interdependency between the surgical technique and the postsurgical course of rHb values. Abstract: Purpose: Wound healing complications are a major concern after open reduction and internal fixation (ORIF) in patients with calcaneal fractures. Microcirculation is known to play a key role in bone and soft tissue healing. The present study aimed to characterize and contrast the dynamics of changes in microcirculation comparing two different surgical procedures: A) ORIF and B) a minimally invasive approach (MIA). Methods: Blood flow (BF[AU]), oxygen saturation (sO2 [%]) and relative amount of haemoglobin (rHb[AU]) were measured at two depths (2 mm and 8 mm) non-invasively by spectrophotometry (Micro-Lightguide O2C®, LEA Medizintechnik, Giessen, Germany) before surgery and every 24 h after surgery for a duration of six days. A linear mixed model (LMM) was used to analyse longitudinal data and repeated measurements. Results: Nineteen patients (44 years, range 21.9–71.0 years) were enrolled in the study. Surgical treatment consisted of ORIF ( n  = =15) and MIA ( n  = =9). The postoperative BF and sO2 at the 2 mm and 8 mm depths were higher in the ORIF group (BF: p  < 0.001, p  = =0.003; sO2 : p  = =0.001, p  = =0.011). The BF at the 2 mm and 8 mm depths increased after surgery (2 mm: p  = =0.003, 8 mm: p  = =0.001) in both groups. This increase did not correlate with the surgical technique. sO2 and rHb values at the 8 mm depth decreased after surgery (sO2 : p  = =0.008, rHb: p  < 0.001) in both groups, whereas sO2 at the 2 mm depth increased after surgery ( p  = =0.003). Furthermore, the surgical technique correlated with the postsurgical course of sO2 values at the 2 mm depth ( p  = =0.042). Conclusions: The spectrophotometry results were in line with the generally accepted phases of soft tissue wound healing. Postsurgical changes in microcirculation are predominantly independent of surgical techniques and may be primarily determined by wound and fracture healing. Future studies should focus on the potential of spectrophotometry to monitor wound healing after surgery. Moreover, studies with longer observation periods are needed in order to examine the changes in microcirculation during all wound-healing phases.